Obtaining and estimating the potential of protein nutraceuticals from highly mineralized collagen-containing beef raw materials - N. Yu. Mezenova; S. V. Agafonova; O. Ya. Mezenova; L. S. Baidalinova; T. Grimm (Теория и практика переработки мяса)
Highly mineralized collagen-containing beef raw materials (tibia, fibula and costal bones) are a source of valuable protein nutraceuticals. They include high molecular weight proteins, oligopeptides and amino acids, which anabolic and physiological potential is used insufficiently. Protein nutraceuticals were obtained by high-temperature hydrolysis of beef raw materials in combination with enzymolysis by proteolytic enzyme preparations Alcalase 2,5 L, Protamex, Protosubtilin G3x. The water-soluble fraction of hydrolysates was studied after its separation and freeze-drying on the content of nitrogenous compounds, fats, minerals, formol-titrated nitrogen, fractional molecular composition. The mathematical dependencies of accumulation of low molecular weight products of protein hydrolysis on enzymolysis duration and doses of different enzyme preparations were obtained. The rational technological scheme of complex processing of beef raw materials with production of protein, fat and mineral-protein additives was proposed. The protein weight fraction in the freeze-dried protein hydrolysates was 69.5–89.6%. All studied protein additives contained peptides with a molecular weight of not more than 100 kDa. The content of low-molecular weight oligopeptides with a molecular weight of less than 10 kDa in the protein additives obtained by enzymatic thermal hydrolysis was more than 90%. The amino acid composition of protein additives produced by different hydrolytic methods was analyzed. Sensory and functional-technological properties of freeze-dried protein compositions were studied. The amino acid potential, high assimilability and physiological activity of protein nutraceuticals from collagen-containing beef raw materials were established. It is recommended to use them in the composition of specialized biologically active additives (BAAs) to food of the osteotropic direction in recipes of specialized and personalized products as a source of amino acids and active peptides.